PEMBUATAN TEPUNG LIDAH BUAYA DENGAN MENGGUNAKAN BERBAGAI MACAM METODE PENGERINGAN - .,, Latifah; Apriliawan, Angga (REKAPANGAN, 2009)
PEMBUATAN TEPUNG LIDAH BUAYA DENGAN MENGGUNAKAN BERBAGAI MACAM METODE PENGERINGAN